HIV assisted partner services (aPS) to support integrated HIV and hypertension screening in Kenya: a pre-post intervention study - Beatrice Wamuti; Betsy Sambai; Christine Magambo; Margaret Ndegwa; Paul Macharia; Tecla M.Temu; Carey Farquhar; David Bukusi (BMC, 2023)
Abstract Background People living with HIV (PLWH) have a higher risk of developing hypertension compared to HIV uninfected individuals. HIV assisted partner services (aPS), where PLWH are assisted by a healthcare provider to disclose their status to sexual and / or drug injecting partner(s), offers an opportunity for integrated HIV and hypertension screening. We evaluated the feasibility of the aPS model in supporting integrated HIV and hypertension screening at the Kenyatta National Hospital, Kenya. Methods Between August 2019 and December 2020, we conducted a pre-post intervention study. We enrolled women receiving HIV testing services (HTS) with confirmed hypertension (female index clients) and traced their male relatives for HIV and hypertension screening and reviewed management at 3-months. Hypertension was defined as systolic blood pressure (SBP) ≥ 140 mmHg, diastolic blood pressure (DBP) ≥ 90 mmHg, and/or use of antihypertensive medication. Results One hundred female index clients (median age: 55 years; interquartile range (IQR): 47-65) mentioned 165 male relatives (median: 49 years; IQR: 40-59) of whom 35% (n = 58/165) were enrolled. Of the male relatives, 29% had hypertension (n = 17/58), 34% had pre-hypertension (n = 20/58), and none were HIV-positive (n = 0/58). Among the female index clients, there was a statistically significant decline in SBP (pre: 156 mmHg, post: 133 mmHg, p-value: < 0.0001) and DBP (pre: 97 mmHg, post: 80 mmHg, p-value: < 0.0001), and increase in antihypertensive medication uptake (pre: 91%, n = 84/92; post: 98%, n = 90/92; X 2: 4.3931, p-value: 0.036) relative to baseline. Among the male relatives, there was a statistically significant increase in antihypertensive medication uptake among those with hypertension (pre: 13%, n = 6/46; post: 17%, n = 8/46; X 2: 32.7750, p-value: < 0.0001) relative to baseline. Conclusion HIV aPS holds promise for integrated HIV and hypertension screening among at-risk clients and their families. Twenty-nine percent of the male relatives had hypertension, higher than the national prevalence (24%), while one-third had pre-hypertension. We observed relatively high participant retention, reductions in blood pressure, and increase in antihypertensive medication uptake among those with confirmed hypertension. Future research expanding the aPS model to other non-communicable diseases through larger studies with longer follow-ups is required to better assess causal relationships and optimize integrated service delivery.